Foreword: Territorial governance in the Western Balkans: Multi-Scalar approaches and perspectives - Cotella, Giancarlo; Toto, Rudina (European Spatial Research and Policy, 2021)
Since the beginning of the 1990s, the Western Balkans have embarked on a complex path of transition and societal transformation, that was intended to eventually lead to their integration into the European Union. The pace of this process has, however, varied, with some countries already having acquired membership, while others still struggling. Territorial governance plays a particularly important role in this process, as the internal cohesion of the region is key to its successful integration into the EU. However, knowledge on territorial governance in the Western Balkans is still limited and fragmented. This special issue aims to shed some light on the matter, discussing territorial governance contexts and practices in the Western Balkans from a multi-scalar perspective. This editorial serves as an introduction to the special issue, framing its context and guiding the reader through the articles that follow.